DEVELOPMENT CUSTOMER KNOWLEDGE MANAGEMENT (CKM) MODELS IN PURBALINGGA HOSPITALITY USING SOFT SYSTEMS METHODOLOGY (SSM) - Nur Chasanah; Dana Indra Sensuse; Jonathan Sofian Lusa (Faculty of Computer Science Universitas Indonesia, 2014)
Abstract Development of the tourism sector is part of the national development efforts that are being implemented in Indonesia. This research was conducted with the customer to make an overview of knowledge management models to address the existing problems in hospitality in the hospitality Purbalingga as supporting tourism Purbalingga. The model depicts a series of problem-solving activities that result in the hospitality, especially in Purbalingga. This research was action research with methods of Soft Systems Methodology (SSM) with validation using a theoretical approach, expert judgment and user on the object of research. From the research conducted, has produced a model of customer knowledge management in the hospitality tailored to the problems and needs of the hospitality in Purbalingga.